Felix Aderca – scriitorul sub vremuri - Mihaela Iancu (Revista de Istorie și Teorie Literară)
F. Aderca was well known by the inter-war Romanian readers especially for his articles and polemics published in some of the most important newspapers, magazines and reviews of the age. In spite of that activity, which used to pass as his trademark, F. Aderca also wrote thousands and thousands of pages of prose, poetry, drama and essays, he supported and popularized in his articles the modernist literary trends coming from the Western cultures and was a notable member of the modernist Romanian literary cenacle, Sburătorul. His creative effort proved to be unceasing throughout his fifty-year-long career, despite the unfavourable historical times in which he lived: being a Jew, he had to pass through a period of antisemitic policy immediately before and during World War II and he also experienced probably the most aggressive years of the communist regime in Romania under the rule of Gheorghe Gheorghiu-Dej. By starting from F. Aderca’s life and his repeated conflicts with the authorities, this paper aims at discussing the condition of the artist and scholar under a dictatorial or discriminatory regime.